'I See the Site of the Old Colliery Every Day': Scotland's Landscape Legacies of Coal. (2nd January 2020) - Mills, Catherine; McIntosh, Ian
ABSTRACT: This article examines how landscapes of abandoned collieries in central Scotland are used, understood and experienced within the context of de-industrialisation and its lingering effects. A mixed research methodology was adopted that consisted of an on-line questionnaire, face to face interviews and on site observations, together with two case studies focusing on the Polmaise colliery site at Fallin (Stirlingshire) and the Devon colliery at Fishcross (Clackmannanshire). Analysis of the data revealed ambivalent and more complex relationships with the sites than the current literature suggests, and the strength and nature of these associations are dependent on the local topography, the socio-economic history of the site, and time.